Can online learners obtain sufficient competencies in the hospitality and tourism industries? - Sincharoenkul, Kris; Witthayasirikul, Chotima (Frontiers in Education, 2022)
The educational sector has been affected by the COVID-19 pandemic such as the forced adaptative of online classes and the student’s lack of interaction and experience from practical classes. Since the hospitality and tourism industries require professional operations between guests and employees, this may bring a concern to students, who encountered online classes during the pandemic, whether they have sufficient competencies to be recruited into the workplace. . However, the internship offers benefits to higher education institutions, industries, and students to examine the sufficiency of students’ competencies in the workplace. Thus, this study aims to determine the competencies of online-learnt students that influence satisfaction in the employability of the hospitality and tourism industries post-COVID-19. The logistic regression models were established to predict the likelihood of competencies toward each satisfaction attribute. d. The empirical results showed that among five recruitment attributes, the competencies provided a predictor likelihood on three attributes: Foundation, Employability, and Adaptative, while it has no likelihood on Knowledge. The collaboration attribute reported the insignificant regression model. Moreover, only internship experience provided a significant result towards the Adaptive attribute. Also, the discussion and practical implications were provided in this study.